2015
DOI: 10.1002/ajhb.22739
|View full text |Cite
|
Sign up to set email alerts
|

Association between age at menarche and autistic traits in Turkish university students

Abstract: These findings suggest that there may be a common developmental mechanism between delayed menarche and autistic traits, possibly through elevated levels of prenatal androgens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…Two prior findings, association between early AAM and PD 1 , 2 and positive correlation between autistic traits and AAM, 31 would suggest finding lower autistic traits in women with PD, contrary to the results of this study. In our sample, AAM was lower in women with PD; however, this difference was not significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Two prior findings, association between early AAM and PD 1 , 2 and positive correlation between autistic traits and AAM, 31 would suggest finding lower autistic traits in women with PD, contrary to the results of this study. In our sample, AAM was lower in women with PD; however, this difference was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“… 30 Recently, an association between higher autistic traits and delayed menarche was reported in nonclinical female university students. 31 Ingudomnukul et al 14 and Pohl et al 15 have demonstrated the relationship between autism and dysmenorrhea in clinically diagnosed ASD samples. The current study found a similar association in typically developing females.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that as the sample matures, other more relevant findings related to pubertal onset may emerge altering the interpretation of these findings. For example, some previous studies have found delayed pubertal onset [Harper & Collins, 1979;Herguner & Herguner, 2016;Knickmeyer et al, 2006;Whitehouse et al, 2011] or no differences in pubertal timing [May et al, 2017]. Therefore, results from the current study must be interpreted with reasonable caution.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, an increase in premenstrual syndrome has been observed in women with ASD (Obaydi and Puri, 2008; Hamilton et al, 2011), who are more likely to exhibit behavioral issues related to the onset of periods (Burke et al, 2009). In addition, delayed age of menarche seems to correlate with the severity of autistic traits (Hergüner and Hergüner, 2016). These findings lend support to the androgen theory of ASD, according to which elevated levels of testosterone during fetal development may contribute to the development of ASD.…”
Section: Domestic Traits In the Asd Phenotypementioning
confidence: 99%